2016
DOI: 10.6061/clinics/2016(04)11
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity C-Reactive Protein and Cardiovascular Disease Across Countries and Ethnicities

Abstract: Despite substantial differences in ethnicities, habits, cultures, the prevalence of traditional cardiovascular risk factors and affordable therapies, atherosclerosis remains the major cause of death in developing and developed countries.However, irrespective of these differences, inflammation is currently recognized as the common pathway for the major complications of atherosclerosis, stroke, and ischemic heart disease. A PubMed search was conducted for “high-sensitivity C-reactive protein” (hs-CRP) in combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 66 publications
5
65
0
1
Order By: Relevance
“…Indeed, many cardiovascular events occur in individuals with plasma cholesterol concentrations at or below the National Cholesterol Education Program thresholds (Packard & Libby, 2008). Among the several biomarkers that have been proposed for cardiovascular risk stratification, hs-CRP appears to contribute to the identification of people at risk of developing CVD (Fonseca & Izar, 2016). Data from the current study confirms that the high hs-CRP levels associated with diabetes, that is, the third and fourth hs-CRP quartiles characterized by high percent of diabetic patients compared to the lowest hs-CRP quartiles.…”
Section: Discussionsupporting
confidence: 76%
“…Indeed, many cardiovascular events occur in individuals with plasma cholesterol concentrations at or below the National Cholesterol Education Program thresholds (Packard & Libby, 2008). Among the several biomarkers that have been proposed for cardiovascular risk stratification, hs-CRP appears to contribute to the identification of people at risk of developing CVD (Fonseca & Izar, 2016). Data from the current study confirms that the high hs-CRP levels associated with diabetes, that is, the third and fourth hs-CRP quartiles characterized by high percent of diabetic patients compared to the lowest hs-CRP quartiles.…”
Section: Discussionsupporting
confidence: 76%
“…Although procalcitonin is primarily used to help guide physicians to support the presence of bacterial infections, previous research has reported slightly elevated procalcitonin levels during localized bacterial infection and viral infection [15] . In a recent review, hs-CRP was reported to be a valid tool to identify people at a risk of cardiovascular events independent of their demographic background [16] . Xie et al [17] suggested that hs-CRP is associated with internal carotid artery occlusion in ischemic stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, the AHA/CDC panel recommended a significant need to study ethnic differences in CRP concentrations (Doran, Zhu, & Muennig, 2013;Nazmi & Victora, 2007). Based on population-based studies, most white individuals had the lowest CRP concentrations, but African-Americans, South Asians, and Hispanics showed the highest concentrations (Fonseca & Izar, 2016;Ford et al, 2003;Nazmi & Victora, 2007). The level of CRP in African-Americans was higher than that in white individuals (median, 3.0 vs. 2.3 mg/L; p < 0.001), whereas white women, African American women, and black men, all had higher CRP levels in comparison with white men, and the highest levels were observed among black women.…”
Section: Racial/ethnicmentioning
confidence: 99%